Natural Rock Phosphate: A Sustainable Solution for Phosphorous Removal from Wastewater. (2016) - Troesch, Stéphane; Esser, Dirk; Molle, Pascal
Abstract: In application of the European Water Framework directive aiming to achieve a "good ecological status" for all waters, phosphorous removal from domestic wastewater can be of importance before discharging into natural receiving bodies, especially for small communities localized upstream of catchment areas or in zones sensitive to eutrophication. As rural communities in France often choose to treat their wastewater with extensive treatment systems such as constructed wetlands, because these natural processes are easy to operate, equivalent P-removal technologies have been asked for. Research has therefore focused on adsorption or precipitation mechanisms on specific reactive materials. In this context, recent studies undertaken by Irstea (French public research institute, formerly Cemagref) in collaboration with SINT and Epur Nature have shown the interest of natural rock phosphate (apatite) as an efficient and sustainable solution for phosphorous removal from wastewater. Epur Nature (Syntea group) has recently developed and patented a specific filter configuration filled with apatite pellets for high phosphorous removal efficiencies (P outflow concentrations < 2 mg P/L). The mechanisms and key factors for an optimal treatment (apatite quality, particle size, kinetics) are explained and synthetized in the paper. The results from lab scale columns and first results rom full scale wastewater treatment plants in operation since several years are also presented. Finally the possible reuse of the apatite enriched with P from wastewater after 10 to 20 years of operation will be discussed.